Oxidative-Stress Related Gene Polymorphism in Endometriosis-Associated Infertility - Traian Irimia; Lucian Pușcașiu; Melinda-Ildiko Mitranovici; Andrada Crișan; Mihaela Alexandra Budianu; Claudia Bănescu; Diana Maria Chiorean; Raluca Niculescu; Adrian-Horațiu Sabău; Iuliu-Gabriel Cocuz; Ovidiu Simion Cotoi (Medicina, 2022)
Background and Objectives: Endometriosis is a benign inflammatory disease associated with infertility and chronic pelvic pain, estimated to affect 7–10% of reproductive-age women, with the possibility of malignant transformation. Recent studies focus on oxidative stress and genetic mutations as risk factors in the pathophysiology of endometriosis-associated infertility. Materials and Methods: This case-control study is the first in Eastern European women that aimed to investigate four genes’ genetic polymorphisms that encode antioxidant enzymes involved in oxidative stress (glutathione peroxidase 1, GPX1 198Pro > Leu, catalase CAT-262C > T, glutathione S-transferase M1, and T1 null genotype) and their association with endometriosis-related infertility. We compared 103 patients with endometriosis-associated infertility with 102 post-partum women as the control group. Results: The endometriosis group had a mean age of 34.5 +/− 6.12 years, while the control group’s mean age was 35.03 +/− 5.95 years. For CAT-262C > T polymorphism, the variant genotypes were significantly more frequent in the endometriosis group. Moreover, for the GPX1 198Pro > Leu, the endometriosis group had significantly more frequent CT and TT genotypes. The null genotype of GSTM1 was detected significantly higher in the endometriosis group. No significant differences were found in the frequency of GSTT1 between the two groups. This study suggests that GPX1 198Pro > Leu, CAT-262C > T, and GSTM1 polymorphisms may be risk factors and that the association between the GSTM1-GSTT1 null genotype may play a significant role in endometriosis-associated infertility. Moreover, this study suggests that the GSTT1 null genotype does not influence the disease. Visual identification of endometriotic lesions with microscopic confirmation is the accepted gold standard for diagnosing endometriosis, but general anesthesia and laparoscopy are required. Conclusions: In this regard, a panel of genetic or laboratory markers is needed for the early diagnostics of this prevalent disease, especially in the case of young patients with future pregnancy intention.